Multi-Modal Synergistic 99mTc-TRODAT-1 SPECT and MRI for Evaluation of the Efficacy of Hyperbaric Oxygen Therapy in CO-Induced Delayed Parkinsonian and Non-Parkinsonian Syndromes - Skye Hsin-Hsien Yeh; Chuang-Hsin Chiu; Hung-Wen Kao; Ching-Po Lin; Yu-Hus Lai; Wen-Sheng Huang (MDPI AG, 2022)
Background: Delayed neuropsychiatric syndrome (DNS) is characterized by motor dysfunction after acute carbon monoxide (CO) poisoning. We examined the relationship between dopamine transporter (DAT) loss using kit-based Tc-99m-TRODAT-1 (DAT single-photon emission-computed tomography (SPECT) radioligand) and globus pallidus necrosis on MRI, DAT availability before and after hyperbaric oxygen therapy (HBOT), and feasibility of Tc-99m-TRODAT-1 as an index for parkinsonian syndrome in CO poisoning. Methods: Twenty-one CO-intoxicated patients (mean ± SD age, 38.6 ± 11.4; range, 20-68 years) with DNS underwent Tc-99m-TRODAT-1 SPECT and MRI before HBOT and follow-up Tc-99m-TRODAT-1 SPECT to assess DAT recovery. Neurological examinations for Parkinsonism were performed after development of DNS. Results: Over 70% (15/21) of DNS patients showed globus pallidus necrosis on MRI. Significantly lower bilateral striatal DAT availability was associated with globus pallidus necrosis (p < 0.005). Moreover, 68.4% (13/19) of DNS subjects with Parkinsonian syndrome had lower bilateral striatal DAT availability vs. non-parkinsonian subjects pre- or post-HBOT. The SURs for both striata increased by ~11% post-HBOT in the Parkinsonian group; however, the left striatum presented a significantly higher DAT recovery rate than the right (*** p < 0.005). Conclusions: Coupled Tc-99m TRODAT-1 SPECT and MRI could assist evaluation of Parkinsonism risk and indicate DAT availability after HBOT in CO-poisoned patients with DNS.